Atmospheric NO2 dynamics and impact on ocean color retrievals in urban nearshore regions. Issue 6 (19th June 2014) - Tzortziou, Maria; Herman, Jay R.; Ahmad, Ziauddin; Loughner, Christopher P.; Abuhassan, Nader; Cede, Alexander
Abstract Urban nearshore regions are characterized by strong variability in atmospheric composition, associated with anthropogenic emissions and meteorological processes that influence the circulation and accumulation of atmospheric pollutants at the land‐water interface. If not adequately corrected in satellite retrievals of ocean color, this atmospheric variability can impose a false impression of diurnal and seasonal changes in nearshore water quality and biogeochemical processes. Consideration of these errors is important for measurements from polar orbiting ocean color sensors but becomes critical for geostationary satellite missions having the capability for higher frequency and higher spatial resolution observations of coastal ocean dynamics. We examined variability in atmospheric NO2 over urban nearshore environments in the Eastern US, Europe, and Korea, using a new network of ground‐based Pandora spectrometers and Aura‐OMI satellite observations. Our measurements in the US and in Europe revealed clear diurnal and day‐of‐the‐week patterns in total column NO2 (TCNO2), temporal changes as large as 0.8 DU within 4 h, and spatial variability as large as 0.7 DU within an area often covered by just a single OMI pixel. TCNO2 gradients were considerably stronger over the coastal cities of Korea. With a coarse resolution and an overpass at around 13:30 local time, OMI cannot detect this strong variability in NO2, missing pollution peaks from industrial and rush hour activities. Observations were combined with air quality model simulations and radiative transfer calculations to estimate the impact of atmospheric NO2 variability on satellite retrievals of coastal ocean remote sensing reflectance and biogeochemical variables (i.e., chlorophyll and CDOM).